Bibliometric insights into molecular and bioinformatic research trends on ameloblastoma - Yoithapprabhunath Thuckanaickenpalayam Ragunathan; Ramdas Madhavan Nirmal; Supriya Kheur; Kumar Chandan Srivastava; Swetha Pasupuleti; Srichinthu Kenniyan Kumar; Armen A. Muradyan; Artak Heboyan (Discover Oncology)
Abstract Objectives The study aimed to evaluate the significant trends of advancement in the body of literature of specialty journals on molecular biological investigations of ameloblastoma (AB). Additionally, this bibliometric study sought to identify the authors, organizations, journals, and countries from emerging regions that have exerted the most significant influence on molecular biological and bioinformatics studies on AB. Novelty of study The novelty of this study lies in its comprehensive bibliometric integration of bioinformatics and molecular perspectives, offering a structured roadmap for future ameloblastoma research. Materials and methods A complete list of AB molecular biological research citations was found in Scopus. The search was restricted to papers published between 2014 and 2024, but there were no restrictions on the language or type of research studies. The study examined total citations, citation density, journal name, impact factor, journal category, quartile, published year, authors, affiliations, and study type. Results The analysis included collecting 112 publications published between 2014 and 2024. There were 95 original research papers, 6 systematic reviews, 5 case reports, 3 brief communications, and 6 systematic reviews and meta-analyses. Our analysis identifies noteworthy authors and nations that have contributed, with Brazil emerging as a leading figure in this field of study. Conclusions The research on AB, especially its biological profile, has changed significantly across the years, as can be observed by perusing the contents of the papers included here. The data from this study would help the researchers target specific objectives for future research in more relevant avenues.